A comparative study of metabolic profile in pre-eclampsia and normotensive preterm pregnancy - Kothapalli, Durgavathi; Kolluru, Kameswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hypertensive disorders of pregnancy are important and common cause of severe acute morbidity, long-term disability and death among mothers and babies. The metabolic characteristics (hypertriglyceridemia, hyperinsulinemia, hyperuricemia, low HDL2 cholesterol) in pregnancy-induced hypertension resemble the main features of the “insulin resistance syndrome”. This may result in endothelial cell dysfunction as evidenced by PGI2 suppression. We have designed this study with an objective to compare the metabolic parameters like fasting and post prandial blood glucose, fasting plasma insulin, HOMA-IR and lipid profile between pre-eclampsia and normotensive pregnant women at late preterm (32-36 weeks). Methods: Based on enrolment criteria and statistical analysis 224 patients were enrolled in study during study period and divided in to two groups, group 1- normotensive subjects, group2- pre-eclampsia subjects. Various biochemical parameters and obstetric profile was measured and compared with standard normotensive subjects. Results: The mean fasting plasma insulin was significant higher in group 2 than group 1 (18.36±6.48 mIU/dl versus 3.42±1.68 mIU/dl) (p=0.0001). The mean value of HOMA-IR was significant higher in group 2 than group 1 (3.82±1.68 versus 1.98±1.68) (p=0.0001). The mean value of HDL was significant higher in group 1 than group 2 (42.56±3.28 mg/dl versus 34.26±3.63 mg/dl) (p=0.0001). The mean concentration of LDL was significant higher in group 2 than group 1 (142.23±24.36 mg/dl vrsus 84.32±18.24 mg/dl) (p=0.0001). Conclusions: Systolic and diastolic blood pressure was significantly higher in preeclampsia patients and plasma fasting glucose was higher in normotensive subjects. In present study fasting plasma insulin and HOMA-IR are significantly higher in cases then control. Dyslipidemia is significantly evident in preeclampsia patients in our study.